RESPONSE OF SOME MAIZE VARIETIES (Zea mays L.) TO BORON FOLIAR APPLICATION UNDER SIWA OASIS CONDITIONS - H. Hassan; M. Hassaan; M. Attia (Arab Universities Journal of Agricultural Sciences, 2019)
Two field experiments were conducted in two successive seasons; 2017 and 2018 at Bahi ElDin, Siwa Oasis, Egypt, to study the effect of four boron levels (0, 23, 46 and 69 ppm) as foliar application on yield and its components of five maize (Zea mays L.) hybrids (Single Crosses 124, 168, Three Way Crosses 310, 324 and 352). The experimental design was perpendicular strips plot with three replicates. Results indicated that effect of boron and hybrids on plant height, no. of grains/row, ear length, no. of rows/ear, ear diameter, 100-grain weight, grain, ear and stover yields (kg fed-1) were significant. Maize hybrid S.C. 124 produced the highest values of 100-grain wt., grain and ear yields per fed. Maximum no. of grains/row, ear length and stover yield fed-1 were recorded by TWC 324 hybrid. While, TWC 352 hybrid surpassed in no. of rows/ear and ear diameter. Foliar application by 69 ppm boron significantly produced more grains per row and ear, 100-grain wt. and grain yield/fed. Interactions were significant for all studied traits, except no. of grains/row and ear diameter. Thus, it could be concluded that applying 69 ppm boron as foliar for S.C.124 hybrid could be used successfully for improving maize productivity under Siwa Oasis conditions.